INFLUENCE OF В-LYMPHOCYTES ON BONE MARROW RECOVERY OF THE IRRADIATED RECIPIENTS OF ALLOGENIC MIELOTRANSPLANT - Popov, N.N.; Romanova, E.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The study of influencing of enriching allogenic mielotransplant by B-lymphocytes on recovery of hemopoiesis and immunogenesis of the irradiated recipients and possibility of development at them GVHD was the purpose of work. It is rotined that application of В-lymphocytes is joint with mielocariocytes renders a stimulant effect on renewal total organcellularity, number of CFU, lymphocytes of bone marrow of the lethally irradiated recipients. Adding of В-lymphocytes to allogenic T-depleted mielotransplant is instrumental in forming of tolerance to the donor cells and establishment of cellular chimerism.